PEMETAAN KONSEP, PRINSIP, MEKANISME, DAN ELEMEN PAPER ENGINEERING - Vanessa Yusuf; Hafiz Aziz Ahmad; Dianing Ratri (Fakultas Seni Rupa dan Desain ITB, 2021)
Paper engineering or often referred to pop-up has been growing and gaining popularity among people. Yet, until todaythere have been no well-structured mapping made in the study of paper engineering as done in other studies in art anddesign. This research, therefore, aims to map the concept, principle, mechanisms, and elements of paper engineering forcreators and people who are interested in exploring the art of paper engineering to learn. The research is done throughliterature study, either from books or the internet; it was taken from interviews with professional paper engineers inIndonesia. Based on the results of this research, the principle of paper engineering consists of five principles: interactivity,compact, consistency, flexibility, and surprise. The mechanism of paper engineering can be classified into two categories:the movement and the form of the mechanism. The study also reveals that the whole mechanism of paper engineeringconsists of four types of elements: the base page, the object being moved, the moving object, and the builder element.The results of this research can be used as a study reference about the art of paper engineering for students, teachers,practitioners, and fans of paper engineering art.